Pengimplementasian Fitur Data Profiling Pada Aplikasi Data Governance Berbasis Open Source Tools dengan Metode Itterative/Incremental - Ekky Chandra Wibowo; Tien Fabrianti Kusumasari; Ekky Novriza Alam (Journal of Information System Research (JOSH), 2022)
Data is one element that is considered important in a business. If the processing is carried out correctly and as needed, the data has high quality. High data quality can have a positive impact, that is, it can create information and knowledge to support decision-making. In fact, many organizations accumulate data without a good data storage or management system and cause the data to become large so that it is difficult to understand and produce information in it that cannot be conveyed properly which makes a decision not have a maximum positive impact. Data Quality Management (DQM) is considered to be able to assist in maintaining quality in the data and ensure that no data is lost or damaged. Quality data is obtained by one of the stages in DQM, namely data profiling, which performs the process of checking the available and stored data to determine a content structure and data quality. The research focuses on implementing the DQM module data profiling feature on the Data Governance website application. This research produces data profiling features that can help people in data processing where the modules produced are value distribution, data completeness, clustering, value similarity and data deduplication.